The Relationship between Intellectual Capital and Entrepreneurship: A Feld Research on the Directors of the Administration of Benghazi University. - بوكر , رندة (Dirasat in Economics and Business, 2017)
The aim of this research is to find out the relationship between intellectual capital in its three dimensions (human, structural and relational) and entrepreneurrship among the directors of the administrations at Benghazi University. The research Society consists of all directors of the University of Benghazi (60). In this context, a questionnaire form was prepared using some previous studies. After the questionnaire was distributed and retrieved, it was found that 47 study forms were filled out by the participants. By subjecting the data and information contained therein for analysis, the study found that there is no significant correlation between intellectual capital in its three dimensions and entrepreneurship among the directors of the administrations at Benghazi University. The results also showed a good practice of the concept of entrepreneurship. The research recommended that attention should be paid to intellectual capital and its three dimensions, because of its importance in achieving outstanding performance. It also recommended increasing administrative awareness of the concept of entrepreneurship in order to upscale the level of the university.